PENGARUH BUDAYA ORGANISASIDAN GAYA KEPEMIMPINAN TERHADAP KINERJA MELALUI KEPUASAN KERJA KARYAWAN ADMINISTRATIF UNIVERSITAS BAKRIE - Insan Harapan Harahap (KENEGARAAN, 2016)
This research was conducted in Bakrie University in South Jakarta. This research aims to find out the effect of organisational culture and leadership style toward performance through job satisfaction administrative employees of Bakrie University. The research was done to 61 respondents who work as administrative employees of Bakrie University. Data processing was done by using SPSS 16 statistical tool with multiple regression analysis model and do multiple test calculation to determine how much the effect of job satisfaction intervene the effect of organisational culture and leadership style. From the result of linear regression data processing, it founds that the organisation culture and leadership style have positive effects both of partially and simultaneously toward job satisfaction and performance. Besides that, by using test, it found that job satisfaction intervene the relationship between organisational culture and leadership style toward performance, with the equation Ŷ = 2.209 + 0.228X1+ 0.280X2+ 0.435X3+ 0.307X3X1+ 0.119X3X+ εKeyword: organisation culture, leadership style, performance, job satisfaction 2